We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
243
1
avatar+4116 

Help.

 Feb 1, 2018
 #1
avatar+102372 
+1

1.  Notice, NSS,  that

 

4/7  * 4/7 * 4/7  * 4/7  =   256  / 2401

 

But also

 

-4/7 * -4/7 * -4/7 * -4/7  =    256 /  2407

 

So.....  (4/7, -4/7)  is correct

 

 

2.   √[ 36 g^6]   =  

 

Write  this as an exponential...it makes it easier to see, IMHO.....so we have

 

(36)^(1/2)  *  (g^6)^(1/2)  =

 

(6^2)^(1/2)  * ( g^3)  =

 

[ use   (a^m)^n   =  a^(m * n) ]

 

6 * g^3

 

 

cool cool cool

 Feb 1, 2018

3 Online Users

avatar